HPV18 E1^E4 is assembled into aggresome-like compartment and involved in sequestration of viral oncoproteins. - Kajitani, Naoko; Satsuka, Ayano; Yoshida, Satoshi; Sakai, Hiroyuki (Frontiers in Microbiology, 2013)
Papillomavirus is the etiological agent for warts and several squamous carcinomas. Skin cancer induced by cottontail rabbit papillomavirus was the first animal model for virus-induced carcinogenesis. The target organ of the virus infection is stratified epithelium and virus replication is tightly regulated by the differentiation program of the host cell. E1^E4 protein is a viral gene product, and although it is considered to be involved in the control of virus replication, little is known about the biological role. We found that HPV18 E1^E4 was assembled into an aggresome-like compartment and was involved in sequestration of virus oncoproteins, which might contribute to the differentiation-dependent lifecycle of papillomavirus.